ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN MOMNESIA PADA IBU HAMIL DI KABUPATEN INDRAMAYU - Nurhayati, Yati; Apriliani, Purwandyarti; Dewina, Meran (Ikatan Bidan Indonesia (IBI), 2021)
Background : Pregnancy brain or momesia usually refers to memory problems, other research shows that pregnant women during pregnancy show memory loss or focus problems. The results of the study by Davies et al. pregnant women had poor memory skills in focusing attention, making decisions, planning and memory (memory). Memory loss appears to start during the first trimester, then stabilize from mid to late pregnancy. The problem of decreasing the focus of attention can affect the comprehension of pregnant women in obtaining health education information. The purpose of this study was to know the number of pregnant women who experience momnesia in Indramayu, to analyze internal factors that influence the momnesia in pregnant women, to analyze internal external factors that influence the momnesia in pregnant women. Method : This study conducted using a sequential explanatory mixed methods with subjects were pregnant women who live in the Margadadi Health Center and Pasekan Public Health Center who are fulfilling the inclusion and exclusion criteria, from March to September 2020 by purposive sampling. Results : The results of quantitative research, found that 9 out of 138 pregnant women experienced symptoms of momnesia in Indramayu. The results of the qualitative study, the factors that influence of momnesia in pregnant women are gestational age, emotional changes, memory loss/self-efficacy, rest patterns, physical activity and husband /family support. Conclusion : The conclusion of this study is 6.52% of pregnant women have symptoms of momnesia in Indramayu. Factors that influence of momnesia in pregnant women are internal factors such as gestational age, emotional changes, memory loss/self-efficacy, and external factors are rest patterns, physical activity and family support.